Too good to be true? Boundary conditions to the use of downward social comparisons in service recovery - Antonetti, Paolo; Crisafulli, Benedetta; Maklan, Stan (SAGE, 2018)
Evidence shows that downward social comparisons (DSCs), messages delivered by frontline employees describing how service experiences turned out even worse for others, can reduce customers’ anger following a service failure. This study contributes to the literature on DSCs and service recovery by highlighting pitfalls associated with the use of these messages in service recovery and showing the conditions necessary for their effectiveness. Building on persuasion knowledge theory, we show that customers draw manipulative inferences about DSCs because of the perceived bias associated with the source of the message and the implicit derogation of a competitor that DSCs entail. To reduce inferences of manipulative intentions, frontline employees should both accompany DSC messages with intense apologies and use self-derogation to reduce the perception that they are criticizing another firm. Past claims on the generalized effectiveness of DSCs need to be revised. Managers should craft social comparison messages carefully to avoid negative reactions from customers. Our research indicates that once adapted to address these concerns, DSCs can be an effective recovery strategy among individuals with a strong need for social comparison information.
Keywords: service recovery; service failure; downward social comparisons; manipulative intentions; persuasion